(untitled) (Global Journal of Medical Research, 2020)
Stridor is commonly seen post decannulation in a tracheostomised patient. Usually it occurs due to airway obstruction secondary to tracheal stenosis, granulation tissue, tracheomalacia. We report a rare case of stridor due to dynamic pharyngeal collapse after decannulation. A 68-year -old male who presented with inferior wall MI and Complete Heart Block had to be put on a mechanical ventilator for hemodynamic instability and subsequently tracheostomised. Post decannulation he developed stridor and breathlessness. CT scan of neck revealed a supraglottic narrowing which on bronchoscopy showed a dynamic collapsibility of supraglottic area. This dynamic collapse was treated with non invasive positive pressure ventilation.